IMPLEMENTASI STANDAR ISO 21001:2018 TERHADAP BUDAYA MUTU DI PERGURUAN TINGGI DENGAN KEPUASAN KERJA DOSEN SEBAGAI VARIABEL MEDIASI - Rasulong, Ismail; Rizal, Samsul; Yusuf, Muhammad; Achsanuddin, Andi Nur (Jurnal Penjaminan Mutu, 2025)
The culture of quality in the college is the ability to build a reputation and achieving the goals of the organization sustainably. The ISO 21001:2018 standard is one of the international quality assurance instruments that is required not only for institutional accreditation but also to ensure that the entire internal processes of the organization are carried out properly and consistently. The study aims to analyze (1) the impact of ISO implementation on a quality culture, (2) the effect of implementation of ISO on lecturer job satisfaction, (3) the influence of lecturer work satisfaction on a Quality culture, and (4) the impact on quality culture through lecturer employment satisfaction. Research method is quantitative research with inferential statistical approaches using structural equation modelling (SEM). The data was collected from 110 lecturers in the area of the Faculty of Economics and Business of Muhammadiyah University of Makassar and then the data was analyzed using Partial Least Square with the help of SmartPLS 3.0 Software. The research findings are that (1) the implementation of ISO 21001:2018 has a positive relationship but its impact is not significant directly on the culture of quality in colleges, (2) the implementations of ISO21001: 2018 have a positive link with a significant direct impact on the satisfaction of the faculty in the university, (3) the dissatisfaction of faculty has a positively related relationship with a substantial direct effect on the quality culture in the college, and (4) ISO 21001:2018 implementations have positive and influential relationships with the Culture of Quality when mediated by faculty satisfaction in the colleges.